A Comparison of Practitioner and Student Writing in Civil Engineering. Issue 2 (17th April 2017) - Conrad, Susan
Abstract: Background: Numerous studies have identified a gap between the writing skills of engineering program graduates and the demands of writing in the workplace; however, few studies have analyzed the writing of practitioners and students to better understand that gap and inform teaching materials. Purpose: This study sought to compare word‐level, sentence‐level, and organizational differences in writing by practitioners and students and to identify differences that are important for engineering practice. I also sought to demonstrate the untapped potential for linguistic analyses to contribute to understanding engineering writing. Design/Method: I used techniques from applied linguistics – corpus linguistics and rhetorical move analysis – supplemented with interviews of practitioners and students. The analysis investigated the interaction of language features, their functions, and writers' motivations. Results: Student writing had more complicated sentence structures, less accurate word choice, more errors in grammar and punctuation, and less linear organization. These characteristics decreased effectiveness in areas that practitioners considered important: accurate and unambiguous content; fast, predicable reading; liability management; and attention to detail. Underlying the student writing problems were misconceptions about effective writing, ignorance of genre expectations, weak language skills, and a failure to appreciate that written words, not just calculations, express engineering content. Conclusions: The findings better define the gap between student and practitioner writing, and are a basis for instructional materials that target important student writing weaknesses.